Nature-based solution for Lambda-Cyhalothrin removal in Ria Formosa contaminated sediment: A mesocosm study - Azanda, Hornam (2024)
Nature-based solutions (NBS) harness natural tools for effective contaminant removal via organism-based processes like phytoremediation. However, in highly contaminated environments, phytoremediation effectiveness may be limited due to pollutant interactions. Microbe-assisted phytoremediation (rhizoremediation) offers a promising alternative for removing pollutants in challenging contaminated settings. The objective of the present project was to evaluate the biodegradation of Lambda-cyhalothrin (LC) of a Ria Formosa salt marsh plant (Spartina maritima) through biodegradation mesocosms of plant, and sediments experiments following the inoculation of contaminated sediments with a LC - degrading rhizospheric bacteria. Experimental setups encompassed various treatments, including phytoremediation, bioaugmentation, and rhizoremediation and different control conditions. Results from the study highlighted substantial LC degradation across all three treatments, indicating a reduction of 30% for Phytoremediation (Phyto), 27% for Combined Phytoremediation and Bioaugmentation (Phyt + BioA), and 22% for Bioaugmentation (BioA) after a 7-day duration. The utilization of Spartina maritima in phytoremediation demonstrated effectiveness in LC degradation within Ria Formosa sediment. Moreover, the combination of Spartina maritima with its rhizospheric bacterial consortium (rhizoremediation) also proved to be an efficient approach for LC degradation and has the potential to facilitate the degradation of the pesticide under highly stressed environment conditions. Future research endeavors should focus on further exploring the potential of these bioremediation techniques under varied environmental conditions and differing contamination levels. This comprehensive exploration will offer invaluable insights into the optimization and applicability of these strategies for LC degradation in diverse ecological contexts.